2001
DOI: 10.1007/s00268-001-0062-z
|View full text |Cite
|
Sign up to set email alerts
|

Orbital and Optic Nerve Trauma

Abstract: The ability to measure orbital volume expansion and correlate this with later enophthalmos has advanced radiological assessment of patients with orbital floor fractures. Attempts have also been made to classify orbital floor fractures on the basis of their configuration on CT scan and to correlate this with outcome in terms of ocular motility. A small subset of relatively undisplaced floor fractures with tight entrapment of tissues occurring most commonly in young patients has been identified, and early surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The results of several retrospective case series 8,21,22 suggest a beneficial effect of systemic corticosteroids, whereas others 3,8,10-12 found improved visual outcome after surgical therapy. Still other series 1,6,9,19,23 have failed to demonstrate any clear-cut benefit of treatment compared with observation alone. The largest prospective comparison study of patients of all ages with TON found no difference in outcome among patients treated with surgical decompression, high-dose steroids, or observation.…”
Section: Discussionmentioning
confidence: 91%
“…The results of several retrospective case series 8,21,22 suggest a beneficial effect of systemic corticosteroids, whereas others 3,8,10-12 found improved visual outcome after surgical therapy. Still other series 1,6,9,19,23 have failed to demonstrate any clear-cut benefit of treatment compared with observation alone. The largest prospective comparison study of patients of all ages with TON found no difference in outcome among patients treated with surgical decompression, high-dose steroids, or observation.…”
Section: Discussionmentioning
confidence: 91%
“…2). Otherwise, the indication for infraorbital canal decompression in this study is very clearly defined, because some authors maintain that it is not clear whether and to what extent the sensibility disorders are only due to trauma, or to tissue manipulation during open surgery (18–20, 37). There is the following indication for infraorbital canal decompression: injury of infraorbital canal following ZMC fracture and ION hypoalgesia.…”
Section: Discussionmentioning
confidence: 98%
“…On one hand, while some favor decompressive exploration and surgical repair of the fissure and optic canal, on the other hand are those suggesting medical treatment. 3 The literature contains many solely case reports and series on the treatment of optic nerve injury. The earlier western literature advised against surgical intervention even though Japanese literature of the 1960s and 1970s suggest that traumatic optic neuropathy was more responsive to surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors advocate emergency nerve decompression, while still others recommend steroid therapy alone or following patients without treatment. 3 We employed the mega dose corticosteroid alone in the treatment of patients with superior orbital fissure and orbital apex syndromes after craniomaxillofacial traumas. This paper summarizes the superior orbital fissure or orbital apex syndromes that have been treated in our clinic in the last 10 years and reports the results obtained with corticosteroid treatment.…”
mentioning
confidence: 99%